Assessing visitor satisfaction with tourism rejuvenation policies: the case of Rimini, Italy - Rinaldo Brau; Antonello Scorcu; Laura Vici (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
In this paper we assess the appeal of potential interventions on the tourism offer of Rimini, a popular Italian seaside holiday destination, by means of a choice modelling analysis. Tourism can be viewed as a composite good, its overall utility depending on the arrangement of the component characteristics. Our discrete choice experiments incorporate as attributes a number of possible changes to current tourist activities (the subject of public debate), including them in hypothetical alternative holiday packages. The conditional logit analysis indicates that tourists show lesser preference for interventions aimed at protecting the environmental integrity of the beach and greater preference for those, such as the creation of a pedestrianised seafront with late-night opening of amenities and facilities, that are likely to diminish the role of the traditional sea, sun and sand component of the overall holiday experience.
Keywords: 330